Against the one-way-street: Analyzing knowledge transfer from industry to science - Heide Fier; Andreas Pyka (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This study aims at analyzing the differences in the factors that influence the probability of knowledge transfer within industry and from industry to science in the biotechnology sector. In order to model these knowledge flows a citation analysis on the basis of patent data was conducted and a weighted bivariate probit model was estimated on the citation probability of industry and science on the basis of a combined sample of citing and cited patent pairs and an equal number of control patent pairs. The empirical results suggest that there are considerable differences in the citation probability. Cultural closeness for instance has a positive effect on the citation probability from industry to industry while the citation probability of scientific institutions is not affected by cultural distance.
Keywords: J61; O33; 330; Technology transfer; patent citation analysis; biotechnology industry; Biotechnische Industrie; Biotechnische Forschung; Forschungskooperation; Wissenstransfer; Technologietransfer; Patent; Publikationsanalyse; Schätzung; Deutschland